Pelanggaran Etika di Universitas Pancasila: Dugaan Pelecehan Seksual Mengguncang Integritas Kampus - Maura Sasqiandini; Nurul Ghefira; Muhammad Athilla Ghifary (Lembaga Pengembangan Kinerja Dosen, 2025)
The alleged sexual harassment case at Pancasila University highlights the importance of implementing ethical values ​​in the academic environment. This study aims to analyze ethical violations that occur, especially in the context of sexual harassment, using ethical theories such as deontology, utilitarianism, and justice theory. The results of the analysis indicate that these violations not only harm the victims individually, but also threaten the integrity, reputation, and trust of the academic community in the institution. The findings also indicate weaknesses in university policies and procedures in handling this case effectively. Therefore, it is necessary to update ethics policies, increase awareness through training, and a transparent and justice-oriented reporting system. With these steps, the university is expected to create a safe, fair, and moral environment for all members of the academic community.